The Effect of Canal Dryness on Bond Strength of Bioceramic and Epoxy-resin Sealers after Irrigation with Sodium Hypochlorite or Chlorhexidine - Razmi, Hasan; Bolhari, Behnam; Karamzadeh Dashti, Negar; Fazlyab, Mahta (Iranian Endodontic Journal, 2016)
Introduction: The aim of this in vitro study was to evaluate the effect of canal dryness on the push-out bond strength of two resin sealers (AH-Plus and Adseal) and a bioceramic sealer (Endosequence BC sealer) after canal irrigation with sodium hypochlorite (NaOCl) and chlorhexidine (CHX). Methods and Materials: A total of 18 extracted human premolars were used. Canals were prepared and were divided to two groups based on irrigation solution (either NaOCl or CHX). The samples were again divided based on pre-obturation canal condition (wet, half-wet and dry). The samples were sub-divided into 3 groups based on the sealer type; the teeth were obturated with gutta-percha and test sealers (Adseal, AH-Plus or BC sealer). A total number of 18 groups were available to be cut into dentine disks (12 disks in each group). The type of bond failure was also assessed in each group. Data were analyzed using the 3-way ANOVA, post hoc Tukey’s tests, t-test and the Fisher’s exact test. The level of significance was set at 0.05. Results: The bond strength of Adseal was not affected by the canal condition or irrigation with either NaOCl or CHX. Although the bond strength of AH-Plus was not affected by the irrigant type, the highest bond strength was seen in dry canals. For Endosequence BC sealer, the canal conditions did not affect the bond strength; however, CHX reduced the bond strength. Conclusion: Bond strength of resin sealers was not affected by irrigation solution; however, canal moisture negatively affected the bond strength of AH-Plus. CHX reduced the bond strength of BC sealer. Keywords: Bioceramic; Chlorhexidine; Epoxy Resin-Based Root Canal Sealer; Root Canal Sealer; Sodium Hypochlorite